Analisa Pengaruh Sistem Pengukuran Kinerja Terhadap Kinerja Manajerial Melalui Kejelasan Peran dan Pemberdayaan Pisikologis sebagai Variabel Moderating - Dwi Sartika (Jurnal Akuntansi dan Keuangan, 2017)
This study examines the influence of Performance Measurement System to Role Clarity, Psychological Empowerment and Managerial Performance. Continuing research by Hall (2004), as for becoming object from this research is manufacturing business which located in Lampung of Indonesia. This research represents the empirical test which used random sampling technics in data collection. Data were collected using a survey of 148 maid chairman private colleges in Lampung, Indonesia. Data analysis uses Structural Equation Model (SEM) with the program SmartPLS (Partial Least Square). Result of hypothesis Examination indicate that from five hypothesis raised, only two accepted hypothesis. Accepted Hypothesis is hypothesis 2 (there are positive influence between Performance Measurement System to Role Clarity) and hypothesis 5 (there are positive influence between Psychological Empowerment to Managerial Performance). While hypothesis 1 (there are no influence between Performance Measurement System to Managerial Performance), hypothesis 3 (there are no influence between Role Clarity to Managerial Performance), hypothesis 4 (there are no influence between Performance Measurement System to Psychological Empowerment) are rejected hypothesis.